Eye color-based computer aided diagnosis system - Abu-Rayyan, Anwar; Sweiti, Remah; Abu-Rayyan, Nour (Palestine Polytechnic University , department of information technology)
A new method to detect the disease in the human body is proposed in this project. Medical studies show that many diseases have indicators in the eye. Based on image processing technology, the application can recognize objects in a given image of the eye, and discover the features that we need to detect the disease, and excludes features that are not needed. Two diseases will be discovered using this application. الملخص طريقة جديدة لاكتشاف الأمراض في جسم الإنسان هو ما نهدف إليه في هذا المشروع, الكثير من الدراسات الطبية أكدت على أن الكثير من الأمراض تظهر أعراض لها في العين. وبالاعتماد على تكنولوجيا معالجة الصور, فإن هذا التطبيق يمكنه تحديد جزء من العين دون الآخر, واكتشاف الخصائص التي يحتاجها لاكتشاف المرض, واستبعاد الخصائص التي لا نحتاجها. وفي هذا النظام سنقوم باكتشاف مرضين من خلال لون العين وهما مرض الوهن العضلي ومرض التهاب الكبد الوبائي.
CD , Number of page 47 , تكنولوجيا المعلومات 1/2014
Keywords: Eye , color , based , computer , aided , diagnosis , system